Presencia y patrones de comportamiento del delfín manchado costero, Stenella attenuata (Cetacea: Delphinidae) en el Golfo de Papagayo, Costa Rica - May-Collado, Laura; Morales Ramírez, Alvaro (Revista de Biología Tropical, 2005)
Dolphins are characterized by a significant behavioral versatility, which allows them to respond to environmental seasonality. Seasonal variation in dolphin behavior in tropical waters is not well known. Stenella attenuata graffmani is a resident dolphin in the clearly defined seasonal Gulf of Papagayo, Costa Rica, and we studied if dolphin group size, occurrence and behavioral patterns were associated with season and time of day in the gulf. Using strip transects we surveyed two locations for three consecutive years. School size ranged from 1 to 50 individuals, mean group size was 10.16 (SD = 9.61) individuals. Overall, foraging activities were the most frequent, followed by social interactions and travel. From 6:00 AM to 9:00 AM we mostly observed social interactions, followed by feeding-socializing (9:00 AM-12:00 PM) and feeding exclusively (12:00 PM-3:00 PM). Social activities intensified afterwards (3:00 PM-6:00 PM). Behavior and gulf seasonality were associated (χ2 = 90.52, gl = 6, p<0.05, n = 99). In the dry season (December-April) feeding predominated over other activities, but socializing was more frequent in the early rainy season (May-July). Larger groups (mean 12 dolphins) forage actively; smaller groups (mean 6 dolphins 6.51 ± 5.12) foraged more passively. Seasonal variation in dolphin activities are likely to be associated with food availability, as observed in the high number of groups involved in foraging behaviors, and a high investment in foraging activities during the dry season.